Role of leader-member exchange and organisational justice on firm sustainability in India: an empirical examination. (20th September 2019) - Lather, Anu Singh; Kaur, Simran
This study proposed that a perception of organisational justice plays an important role in explaining the relationship between subordinates and their supervisors, and in turn, the resulting influence on firm's sustainability. The study reports responses from 218 employees from Delhi NCR. This study disclosed that the distributive, procedural and interactional justice stanching from the leader member exchange quality have a positive and significant link with firm sustainability. The limitations of common method bias and cross sectional data are discussed in light of implications for future research. This study answers the vital question that what should be done to increment the perception about organisational fairness which result in sustainability of the firm.